"It's not a pain you can fix": A qualitative exploration of working with vulnerably positioned current and bereaved carers across sectors of health and social care. - Bindley, Kristin; Lewis, Joanne; DiGiacomo, Michelle (Death Studies, 2026)
Caring for someone with a life-limiting illness is associated with complex psychosocial sequelae; amplified for carers experiencing structural vulnerability. Workers across sectors of health and social care provide support for vulnerably positioned carers, yet exploration of the impacts of this work has predominantly focused on health professionals directly engaged with death and dying. This qualitative study explored ways in which palliative care and welfare workers experience work with current and bereaved carers of people with life-limiting illness, in a region associated with socioeconomic disadvantage. Work in this landscape involved: (1) navigation of evocative content, (2) encountering limits of grief literacy, (3) negotiating effects of policy constraints, (4) meaning-making for system survival, and (5) varied utilization of resources and strategies. Findings indicate the need for cross-sectoral recognition of consequences of this work, reflected through initiatives to cultivate grief literacy, acknowledgement of harmful consequences of policy, and structural approaches to workforce well-being.